Design of bow-tie patch antenna with slot to improve the performance at 2.5GHz / I'Faf Mohd Rodhi - Mohd Rodhi, I'Faf (2016)
This paper presents a design of bow-tie antenna with a rectangular-shape slot on the patch for wireless application. The investigation was carried out with two different design that is a conventional bow-tie antenna and bow-tie antenna with slot on the patch. It was designed to operate with FR-4 substrate (h=1.6mm), with a dielectric constant (= 4.3) operating at frequency of 2.5GHz. The antennas were simulated using CST Microwave Studio. The antenna was fabricated and measured using Vector Network Analyser (VNA) and tested in anechoic chamber to get the radiation pattern. The results shows an increase in performance of the antenna after slot was added. From result measured, the value of return loss increased from -38.23dB to -40.46dB, the frequency shifted to 2.651GHz with bandwidth remains almost invariant after slot was added.